2020
DOI: 10.33545/26643766.2020.v3.i1a.66
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of preloading and Co-loading with ringer lactate for prevention of spinal hypotension in elective cesarean section

Abstract: Background: Prevention of spinal induced hypotension was remained challenge to anaesthesiologist for years as it poses risk to mother as well as baby. Prehydration with various volumes of crystalloid or colloids was attempted in the past variable success rate. Recently the principle of preloading with fluids has been challenged by various studies. This prompted us to evaluate the effectiveness of crystalloid preloading compared to preloading for prevention of spinal hypotension. We evaluated vasopressor requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…19,20 Borse YM, Khan M, Rao A and Oh stating that crystalloid Co-loading is more effective than preloading for prevention of spinal induced hypotension. [20][21][22][23] Verma S et al also found that co-loading i.e. hydration at the time of actual block during LSCS was more efficient in preventing hypotension following spinal anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Borse YM, Khan M, Rao A and Oh stating that crystalloid Co-loading is more effective than preloading for prevention of spinal induced hypotension. [20][21][22][23] Verma S et al also found that co-loading i.e. hydration at the time of actual block during LSCS was more efficient in preventing hypotension following spinal anaesthesia.…”
Section: Discussionmentioning
confidence: 99%